Involvement of the hippocampus, amygdala, entorhinal cortex in memory consolidation - Zanatta, Marilene de Souza (1997)
A total of 182 young adult male Wistar rats were bilaterally implanted with cannulae into the CA1 region of the dorsal hippocampus and into the amygdaloid nucleus, the entorhinal cortex, and the posterior parietal cortex. After recovery, the animals were trained in a stepdown inhibitory avoidance task. At various times after training (0, 30, 60 or 90 min) the animals received a 0.5-μl microinfusion of vehicle (saline) or 0.5 μg of muscimol dissolved in the vehicle. A retention test was carried out 24 h after training. Retention test performance was hindered by muscimol administered into both the hippocampus and amygdala at 0 but not at 30 min posttraining. The drug was amnestic when given into the entorhinal cortex 30, 60 or 90 min after training, or into the parietal cortex 60 or 90 min after training, but not before. These findings suggest a sequential entry in operation, during the posttraining period, of the hippocampus and amygdala, the entorhinal cortex, and the posterior parietal cortex in memory processing.